The pragmatics and Semiotics Analysis of Vinyl Record Cover Art They Fell From The Sky's Album DECADE - Yudhanto, Sigied Himawan; Risdianto, Faizal (State institute of islamic studies salatiga, 2022)
In this study, the researchers focus on the meaning of the DECADE album cover from They Fell From The Sky music band. This was chosen because the artwork used is quite attractive and has This study uses qualitative research with a descriptive method. The analysis was carried out using the semiotic theory of Roland Barthes and the pragmatics theory of John Searle. This study aimed to determine the meaning contained in the cover design of the DECADE album. This research shows that between context signs and visible signs, there is a relationship where the two synergize in the title. The band, namely